Pengembangan Webiste Desa Wisata Sebagai Sarana Promosi Pariwisata dan Produk UMKM Kreatif di Desa Singapadu Tengah - Widiastuti, Ni Luh Ayu; Utami, Nengah Widya; Putra, I Gede Juliana Eka (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The tourism sector is an important indicator in the economic part of a country. Not only providing rapid support for national income, the tourism sector also opens opportunities to generate jobs, increase investment, and introduce cultural tourism and its natural beauty. This research has the purpose of developing websites, activities carried out to carry out development. The method used in this activity is using the System method System Usability Scale (SUS) and pre-test and post-test questionnaires. Based on the results of the score obtained, the Central Singapadu Tourism Village website received a score of 79 and the results of the evaluation using pre-test and post-test to the IT staff of Central Singapadu Village showed an understanding of website content management.